Synthesis of polymer coated iron oxide for the disinfection of bacteria - Tan, Qing Zuan (2021)
Water is an important element in human daily life. However, there are more than 2.2 billion people do not have access to clean and safe drinking water. The presence of pathogenic E. coli in water will cause bloody diarrhea, kidney failure or even death. There are a lot of water treatment techniques to purify the microorganism polluted water. However, these disinfection methods are known to have their downsides including the production of harmful byproducts or high energy consumption. The use of Fenton reaction to remove E. coli had emerged as a promising disinfection technique in recent years. Conventional Fenton reaction which uses iron and hydrogen peroxide (H2O2) as reagents possess limitations such as narrow pH working range or production of iron sludge. Recent research moves towards the use of heterogenous Fenton reaction which uses iron oxide (Fe3O4) and H2O2 as reagents. In addition, the use of polymer to coat on Fe3O4 enhanced the colloidal stability of the core. In this paper, the synthesis and characterization method of polydimethyldiallyl ammonium chloride (PDDA) functionalized Fe3O4, the effect of parameters (pH, catalysts dosage), and comparison with other disinfection techniques were reviewed. PDDA functionalized Fe3O4 can be easily synthesized by insitu or post synthesis coating. The characterization of PDDA functionalized Fe3O4 showed that the coating of PDDA onto the Fe3O4 core would not perturb to original crystallinity of Fe3O4 nanoparticles. By comparing with other disinfection methods, Fenton reaction requires higher cost and disinfection contact time but a comparable efficiency. The most important benefir of Fenton reaction is the environmental friendly nature. Hence Fenton reaction using PDDA functionalized Fe3O4 can be a good alternative in wastewater treatment industry.